Naive T Cells in Graft Versus Host Disease and Graft Versus Leukemia: Innocent or Guilty? - Dekker, Linde; Sanders, Evy; Lindemans, Caroline A.; de Koning, Coco; Nierkens, Stefan (Frontiers in Immunology, 2022)
The outcome of allogeneic hematopoietic cell transplantation (allo-HCT) largely depends on the development and management of graft-versus-host disease (GvHD), infections, and the occurrence of relapse of malignancies. Recent studies showed a lower incidence of chronic GvHD and severe acute GvHD in patients receiving naive T cell depleted grafts compared to patients receiving complete T cell depleted grafts. On the other hand, the incidence of acute GvHD in patients receiving cord blood grafts containing only naive T cells is rather low, while potent graft-versus-leukemia (GvL) responses have been observed. These data suggest the significance of naive T cells as both drivers and regulators of allogeneic reactions. The naive T cell pool was previously thought to be a quiescent, homogenous pool of antigen-inexperienced cells. However, recent studies showed important differences in phenotype, differentiation status, location, and function within the naive T cell population. Therefore, the adequate recovery of these seemingly innocent T cells might be relevant in the imminent allogeneic reactions after allo-HCT. Here, an extensive review on naive T cells and their contribution to the development of GvHD and GvL responses after allo-HCT is provided. In addition, strategies specifically directed to stimulate adequate reconstitution of naive T cells while reducing the risk of GvHD are discussed. A better understanding of the relation between naive T cells and alloreactivity after allo-HCT could provide opportunities to improve GvHD prevention, while maintaining GvL effects to lower relapse risk.